2003
DOI: 10.4049/jimmunol.171.12.6448
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of IL-1α and IL-1β on Tumorigenicity Patterns and Invasiveness

Abstract: In this study, we show that distinct compartmentalization patterns of the IL-1 molecules (IL-1α and IL-1β), in the milieu of tumor cells that produce them, differentially affect the malignant process. Active forms of IL-1, namely precursor IL-1α (pIL-1α), mature IL-1β (mIL-1β), and mIL-1β fused to a signal sequence (ssIL-1β), were transfected into an established fibrosarcoma cell line, and tumorigenicity and antitumor immunity were assessed. Cell lines transfected with pIL-1α, which expresses IL-1α on the memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
153
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(164 citation statements)
references
References 30 publications
7
153
3
1
Order By: Relevance
“…On the contrary, the membrane IL-1α even slightly protected the mice from CCl 4 -induced acute liver injury. It has been suggested that membrane IL-1α could function as an adhesion molecular to promote immune responses [11,50]. The mechanism of its protective role in acute liver injury still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the membrane IL-1α even slightly protected the mice from CCl 4 -induced acute liver injury. It has been suggested that membrane IL-1α could function as an adhesion molecular to promote immune responses [11,50]. The mechanism of its protective role in acute liver injury still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, small amounts of IL-1␣, which is homeostatically expressed in cells, but not secreted, can be poured out from necrotizing cells at the site of carcinogen injection, and serve as a "danger signal" for mounting antitumor cells immunity (46). In contrast, IL-1␤ is only active as a secreted molecule, which is not accumulated in the producing cell; upon secretion, it possibly induces potent and widespread inflammatory responses that override, or even suppress, manifestations of adaptive immunity (21)(22)(23)(24)(25). In experimental models of autoimmune diseases, similar involvement of Th1 and Th17 cells, in induction and perpetuation of the pathogenic inflammatory responses, has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1␤ is only active in its mature secretable form and is thus a good inducer of extensive inflammatory responses. Indeed, we and others have shown that IL-1␤, secreted by malignant cells or host cells in the tumor's microenvironment, contributes to increased tumor invasiveness, tumor angiogenesis and tumor-mediated suppression (21)(22)(23)(24)(25)(26). IL-1␣, in addition to its secreted mature form, is also active in cellassociated forms, i.e., the whole precursor molecule, the pro-piece, which is derived following cleavage of the precursor by calpain, and the functional membrane-associated form.…”
mentioning
confidence: 99%
“…It has been reported that carriers of the IL-1B −31C allele, showed higher plasmatic concentrations of IL-1B than subjects with wild-type IL-1B genotype [14]. Upregulation of IL-1B is involved in tumor-promoting effects such as invasiveness [40], angiogenesis [38], and metastasis [45] and has been recognized as negative prognostic factor, mainly in metastatic cancer [27]. Conversely, an association between peptic ulcer and the IL-1B −31T polymorphism has been described [8,9].…”
Section: Introductionmentioning
confidence: 99%